The Impact of the Just Energy Transition on Job Creation in South Africa: A Case of the Wind Energy Sector - Zondi, Nomvula Beryl (University of the Witwatersrand, Johannesburg, 2024)
South Africa's ratification of the Paris Agreement, an international accord established during the Conference of the Parties (COP21) in December 2015, underscores its dedication to confronting climate change and enacting measures to counteract human-induced global warming. Aligned with numerous other nations, South Africa is actively promoting a just energy transition that prioritises the Sustainable Development Goals (SDGs) established by the United Nations General Assembly on September 25, 2015. This transition entails a shift from reliance on carbon-intensive fuels like coal towards renewable energy sources. Given South Africa's substantial coal reserves—ranking sixth globally coal mining and processing has historically played a central role in the nation's energy sector, industrialisation, and economy, contributing significantly to its GDP and providing employment for up to 150,000 individuals throughout the coal value chain. However, the imperative for an energy transition to mitigate climate change and fulfil the country's National Determined Contributions necessitates structural changes that will inevitably impact socio-economic dynamics. Notably, disruptions in the coal value chain will have profound repercussions on both direct and indirect employment and the communities and local economies reliant on the coal industry. The Integrated Resource Plan (IRP) 2010-2030 outlines South Africa's energy trajectory of increasing renewable energy sources into the energy mix. This study focused on wind energy deployment, with a targeted capacity of 17,742 MW by 2030. It aims to identify critical considerations essential for facilitating a just energy transition that maximises job creation in South Africa. Applying a qualitative research methodology, semi-structured interviews were conducted to gather data, utilising a deductive approach based on predetermined themes derived from existing literature on factors influencing job creation. Findings underscore the importance of addressing policy implementation gaps related to the socio-economic impact of the transition, establishing clear directives for skills development in the low-carbon economy, and prioritising local manufacturing and assembly of turbine components. Moreover, the study highlights wind energy deployment as a catalyst for fostering the development of a low-carbon ecosystem while advocating for exploring broader low-carbon value chains such as green hydrogen to enable new industries and employment opportunities. Finally, the study underscores the need for focused attention and investment in research and development of clean coal technologies, offering a potential avenue for sustainable coal utilisation devoid of adverse greenhouse gas emissions and environmental impacts.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science (Interdisciplinary Global Change Studies), to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Socio-economic impact; Job creation; Renewable energy; Wind energy; Just energy transition; Climate change; Value chain; Manufacturing; Policy; Skills development; UCTD; SDG-13: Climate action; SDG-8: Decent work and economic growth